Msx1 and Msx2 are required for endothelial-mesenchymal transformation of the atrioventricular cushions and patterning of the atrioventricular myocardium - Chen, Yi-Hui (BioMed Central, 2008)
BACKGROUND: Msx1 and Msx2, which belong to the highly conserved Nk family of homeobox genes, display overlapping expression patterns and redundant functions in multiple tissues and organs during vertebrate development. Msx1 and Msx2 have well-documented roles in mediating epithelial-mesenchymal interactions during organogenesis. Given that both Msx1 and Msx2 are crucial downstream effectors of Bmp signaling, we investigated whether Msx1 and Msx2 are required for the Bmp-induced endothelial-mesenchymal transformation (EMT) during atrioventricular (AV) valve formation. RESULTS: While both Msx1-/- and Msx2-/- single homozygous mutant mice exhibited normal valve formation, we observed hypoplastic AV cushions and malformed AV valves in Msx1-/-; Msx2-/- mutants, indicating redundant functions of Msx1 and Msx2 during AV valve morphogenesis. In Msx1/2 null mutant AV cushions, we found decreased Bmp2/4 and Notch1 signaling as well as reduced expression of Has2, NFATc1 and Notch1, demonstrating impaired endocardial activation and EMT. Moreover, perturbed expression of chamber-specific genes Anf, Tbx2, Hand1 and Hand2 reveals mispatterning of the Msx1/2 double mutant myocardium and suggests functions of Msx1 and Msx2 in regulating myocardial signals required for remodelling AV valves and maintaining an undifferentiated state of the AV myocardium. CONCLUSION: Our findings demonstrate redundant roles of Msx1 and Msx2 in regulating signals required for development of the AV myocardium and formation of the AV valves.